Negative CO2 emissions in the lime production using an indirectly heated carbonate looping process - Martin Greco-Coppi; Carina Hofmann; Diethelm Walter; Jochen Ströhle; Bernd Epple (Mitigation and Adaptation Strategies for Global Change, 2023)
Lime is an essential raw material for iron and steel production, in construction and agriculture, in civil engineering, in environmental protection, and in manifold chemical manufacturing processes. To address the problem of unavoidable process CO2 emissions associated with the production of lime, efficient capture technologies need to be developed and implemented. The indirectly heated carbonate looping (IHCaL) process is an efficient candidate for this application because it utilizes lime as the sorbent for the CO2 capture. In this work, a retrofit configuration of this process is presented and analyzed for net negative CO2 emissions. This is done considering different fuels that provide the heat required for the regeneration of the sorbent. The different scenarios were simulated with an AspenPlus® model, key performance indicators were calculated, and the process was compared with other post-combustion capture methods. The results show that net negative CO2 emissions as high as -1805 kgCO2/tCaO, calculated with a state-of-the-art coal power plant energy scenario (ηe = 44.2 %; eref,el = 770 kgCO2/MWhel), can be obtained. This represents an equivalent CO2 avoidance of more than 230% with respect to the reference plant without capture (1368 kgCO2/tCaO). A specific primary energy consumption for CO2 avoided (SPECCA) lower than 1.5 MJLHV/kgCO2,av was achieved for the same energy scenario. Particularly promising results can be accomplished when applying fuels with high biogenic fraction and low specific CO2 emissions, such as solid recovered fuels (SRFs) with a high calorific value.
Keywords: 330; Negative CO2 emissions; Carbonate looping; Indirectly heated; Carbon dioxide removal; Refuse-derived fuels; Solid recovered fuels; Lime production